Prevalence of SARS-CoV-2 antibodies in pediatric healthcare workers - Claudia R. Morris; Patrick Sullivan; Grace Mantus; Travis Sanchez; Maria Zlotorzynska; Bradley Hanberry; Srikant Iyer; Stacy Heilman; Andres Camacho-Gonzalez; Janet Figueroa; Shaminy Manoranjithan; Deborah Leake; et al. (International Journal of Infectious Diseases, 2021)
Objectives: To determine SARS-CoV-2-antibody prevalence in pediatric healthcare workers (pHCWs). Design: Baseline prevalence of anti-SARS-CoV-2-IgG was assessed in a prospective cohort study from a large pediatric healthcare facility. Prior SARS-CoV-2 testing history, potential risk factors and anxiety level about COVID-19 were determined. Prevalence difference between emergency department (ED)-based and non-ED-pHCWs was modeled controlling for those covariates. Chi-square test-for-trend was used to examine prevalence by month of enrollment. Results: Most of 642 pHCWs enrolled were 31-40years, female and had no comorbidities. Half had children in their home, 49% had traveled, 42% reported an illness since January, 31% had a known COVID-19 exposure, and 8% had SARS-CoV-2 PCR testing. High COVID-19 pandemic anxiety was reported by 71%. Anti-SARS-CoV-2-IgG prevalence was 4.1%; 8.4% among ED versus 2.0% among non-ED pHCWs (p < 0.001). ED-work location and known COVID-19 exposure were independent risk factors. 31% of antibody-positive pHCWs reported no symptoms. Prevalence significantly (p < 0.001) increased from 3.0% in April–June to 12.7% in July–August. Conclusions: Anti-SARS-CoV-2-IgG prevalence was low in pHCWs but increased rapidly over time. Both working in the ED and exposure to a COVID-19-positive contact were associated with antibody-seropositivity. Ongoing universal PPE utilization is essential. These data may guide vaccination policies to protect front-line workers.